2006
DOI: 10.1097/01.aids.0000210610.52836.07
|View full text |Cite
|
Sign up to set email alerts
|

Acute renal failure in hospitalized patients with HIV: risk factors and impact on in-hospital mortality

Abstract: Acute renal failure remains common among hospitalized patients with HIV and is associated with chronic kidney disease, liver disease, and increased mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
153
0
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(163 citation statements)
references
References 22 publications
6
153
0
4
Order By: Relevance
“…1 Recent epidemiologic studies have revealed that coinfection with hepatitis C virus (HCV) confers an even greater risk of both acute kidney injury (AKI) and chronic kidney (CKD) disease among individuals infected with HIV. [3][4][5][6][7] AKI is a common complication among both ambulatory and hospitalized HIV-infected patients in the highly active antiretroviral therapy (HAART) era. 3,4 In one study involving hospitalized HIV patients by Wyatt and colleagues, 3 AKI was associated with a 5.83 increased odds of in-hospital mortality.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…1 Recent epidemiologic studies have revealed that coinfection with hepatitis C virus (HCV) confers an even greater risk of both acute kidney injury (AKI) and chronic kidney (CKD) disease among individuals infected with HIV. [3][4][5][6][7] AKI is a common complication among both ambulatory and hospitalized HIV-infected patients in the highly active antiretroviral therapy (HAART) era. 3,4 In one study involving hospitalized HIV patients by Wyatt and colleagues, 3 AKI was associated with a 5.83 increased odds of in-hospital mortality.…”
mentioning
confidence: 99%
“…[3][4][5][6][7] AKI is a common complication among both ambulatory and hospitalized HIV-infected patients in the highly active antiretroviral therapy (HAART) era. 3,4 In one study involving hospitalized HIV patients by Wyatt and colleagues, 3 AKI was associated with a 5.83 increased odds of in-hospital mortality. Franceschini and colleagues 5 examined predictors of AKI among HIV-infected patients and found that coinfection with HCV was significantly associated with AKI, along with male gender, CD4 count less than 200 cells/mm 3 , HIV viral load (VL) greater than 10,000 copies per milliliter, and HAART exposure.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Combinations of potential nephrotoxic drugs can increase risk for kidney injury with examples including vancomycin1 piperacillin/tazobactam, aminoglycosides1cephalothin, NSAIDs1radiocontrast, and cisplatin1aminoglycosides (35)(36)(37)(38)(39). As will be reviewed, the pathway of excretion by the kidney represents another risk for drug nephrotoxicity.…”
Section: Drug Combinationsmentioning
confidence: 99%
“…The epidemiology of AKI in hospitalized HIV-infected patients in the HAART era has also not been extensively analyzed. In fact, few studies have focused on the clinical characteristics of AKI in hospitalized HIVinfected patients in the HAART era [15,16,17,18]. In this chapter, we provide a critical and contemporary review of AKI in hospitalized HIV-infected patients in the HAART era, focusing on the incidence, risk factors, and outcome.…”
Section: Introductionmentioning
confidence: 99%